Roman Denarii from North-Western Hispania, Findings from Castromaior (Lugo). A Contextual, Numismatic and Analytic Approach - Orejas Saco del Valle, Almudena; Montero Ruiz, Ignacio; Álvarez González, Yolanda; López González, Luis Francisco; López Marcos, Miguel Ángel; Rodríguez Casanova, Isabel (Madrider Mitteilungen, 2020)
In 2009, in the frame of the systematic archaeological excavations carried out in Castromaior (Portomarín, Lugo, Spain), an ensemble of eleven Roman denarii, dated between 106 BC and the Augustan period, was found. The house 3, where the coins were located, exemplifies the reforms that characterise the last stage of the hillfort. In fact, archaeological research carried out in Castromaior has brought to light the re-foundation of a former settlement, which was totally renewed in the Second Iron Age. The central area of its upper enclosure was deeply reformed in the 1st century BC, during the last phase of the site. It constitutes one of the rare cases of contextual coin findings in the Northwest of the Iberian Peninsula. We have had the opportunity to undertake a complete study, including the numismatic study and archaeometallurgical analyses (XRF and LIA) of the denarii in order to characterise the origin of the metal employed for minting them. Two other coins found in the site (a denarius and an aes) are also included in this study.